91 Novel ambulatory electrocardiogram (ecg) devices for the investigation of palpitations, pre-syncope and syncope-a local nhs joint working quality improvement project. (6th June 2022) - Nyunt Thinn, Wai Yan Kyaw; Birkhoelzer, Sarah M; Cowan, Elena; Bolam, Helena; Anantharam, Brijesh; Kalra, Paul R; Kirubakaran, Sentil
Abstract : Introduction: Palpitations, pre-syncope and syncope is a common presentation to cardiology services. Short monitoring with conventional Holter monitor or cardiac memo is often not sufficient for the detection of paroxysmal cardiac arrhythmia. The aims of this project were: (i) to demonstrate symptom-rhythm correlation with novel ambulatory ECG devices, (ii) to demonstrate short time to diagnosis for patient presenting with palpitation, pre-syncope and syncope, (iii) to assess patient experience.Method: Patients referred to the local Cardiology Department with symptoms of palpitations were offered an Alivecor Kardiamobile 6L ECG for intermittent monitoring over a 3 months period. Patients with symptoms of pre-syncope or syncope were offered a Wellysis S-patch for continuous monitoring over 21 days. Both devices require connection of a smartphone for their use. ECGs recording were uploaded to a software and analysed by the project team. Patient demographics, diagnosis, time to diagnosis, symptom-rhythm correlation and patient experience were evaluated. Results: Out of 86 patients 11 were excluded who did not have access to a smart phone to connect to monitoring devices. To date 62 out of 75 patients have completed the monitoring period with KardiaMobile (n=40, 64.5%) and S-patch (n=22, 35.5%). Participants' mean age was 51 years (range 18–89), 70% women, mean ejection fraction 54%, 41% did not take any medication. 45% (28/62) experienced symptoms a couple of times per year. Symptom-rhythm-correlation was achieved in 75.8% (47/62). 66.7% (42/62) were in sinus rhythm, 7.9% (5/62) atrial fibrillation, 34% (21/62) had atrial or ventricular ectopics. Mean duration of symptom-rhythm correlation was 40 days (Kardiamobile) for intermittent palpitations, 12 days (S-patch) for evaluation of pre-syncope or syncope. A small number of patients reported issues with either of the devices: difficulty using software 13% (8/62), difficulty with connection 8% (5/62) and skin irritation from ECG patch 11% (7/62). Patient's overall satisfaction was very good or excellent in 79% (49/62) of patients. Conclusion: This project demonstrates the feasibility of using novel devices for the remote investigation of palpitations, pre-syncope and syncope. The short time to diagnosis and high patient satisfaction in patient who often repeatedly present to medical services with intermittent symptoms and subsequent negative conventional Holter monitoring highlights the potential in cost saving through reduction in health care utilization.In addition, the Covid pandemic has spotlighted benefits of remote, ambulatory ECG monitors which will become part of the digital future of cardiology. Competing interests: As part of a join working project Daiichi-Sankyo supported this project with £37, 400 to purchase the devices and software license. Conflict of Interest: NO